Development of Interactive Media on the Human Digestive System (Si CerMa) Based on PBL to Improve Learning Outcomes in Science for Grade 5 Primary School Students - Ria Juhariyani; Sarwanto Sarwanto; Roemintoyo Roemintoyo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The digitisation of education, such as the Chromebook procurement programme by the Ministry of Education, Culture, Research and Technology, is an important indicator of the readiness of educational units to face the challenges of the 21st century. However, the lack of innovation among teachers in utilising this technology has resulted in low student learning outcomes. Therefore, this study aims to review the literature on the development of interactive media on the human digestive system (Si CerMa) to improve the learning outcomes of fifth-grade elementary school students in science. The research method used in this study is the Systematic Literature Review (SLR) method. Data collection was carried out by documenting articles published in the last five years. A total of 20 accredited national and international journal articles obtained from Google Scholar, SINTA, and DOAJ were used in this study. The results showed that Si CerMa media, which contains learning outcomes and objectives, materials and videos, student worksheets based on Problem-Based Learning (PBL), evaluations, and educational games, can significantly improve student learning outcomes. The conclusion of this study is that the interactive Si CerMa media is effective and suitable for use in primary school learning to improve learning outcomes, with the main features being developer profiles, learning outcomes and objectives, material on the human digestive system and its functions, evaluation, and edugames.